Aspects of a three dimensional motion analysis of the volleyball spike in high level competition - Kuhlmann, C.; Roemer, K.; Milani, T. L. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
The purpose of the study was a three dimensional motion analysis of the volleyball spike from position four during competition. Spikes were analysed at a tournament of the European league. Regarding the jump technique, only few athletes performed the discussed coordination pattern of the impulses within the body. It may be concluded that there exists reserves within the training process concerning the coordination in the takeoff phase even in high level athletes.